(untitled) (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is to analyze and to present the most frequent conceptual mechanisms in observing and describing scientific phenomena which allow a successful and efficient exchange of information on the level of communication between the scientific community and the “audience”, and also on the level of communication within the scientific community itself, within the field of information science. Application of conceptual mechanisms in the language of information science is presented through the examples of often, almost daily used terms, such as database, gadget race, information architecture, intellectual property, print revolution, computer virus, artificial life, etc. The observing and describing of these terms has been followed, both in popular discourse (such as on various web pages), as well as in available scientific and professional literature. The work is comprised of four parts. After the basic introductory part on the language of scientific communication, follows the presentation of the conceptual metaphor theory, conceptual integration theory and scientific model. Each conceptual mechanism is followed by the analysis of specific examples from the language of the information science. Taking into consideration that the area of information science is under a constant influence of technological changes and development of modern information – communication technology, new and different phenomena are often observed, and they require a new thinking framework in the process of observation, as well as the new ways of language articulation during the process of their description and communication to the scientific and non – scientific audience. The fundamental contribution of the paper is the display and analysis of few examples of the observed new thought patterns and new ways of language articulation in popular and scientific discourse of the information science language.